2022
DOI: 10.1371/journal.pone.0266633
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal hormone-free moisturising cream is not inferior to an estriol cream for treating symptoms of vulvovaginal atrophy: Prospective, randomised study

Abstract: This prospective, open-label, multicentre, multinational, randomised trial investigated the non-inferiority of treatment with a vaginal hormone-free moisturising cream compared to a vaginal estriol (0.1%) cream in a panel of post-menopausal women suffering from symptoms of vulvovaginal dryness in a parallel group design. In total, 172 post-menopausal women were randomly allocated to either one of the two treatments, each administered for 43 days. The primary endpoint was the total severity score of subjective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In a randomized trial of 172 postmenopausal individuals with vaginal dryness randomized to receive either a hormone-free vaginal moisturizer or vaginal estriol (0.1%) cream, the nonhormonal moisturizer was found to be noninferior to vaginal estriol for symptom improvement in women with mild to moderate symptoms [9 ▪ ]. Though earlier systematic review found that vaginal estrogen was superior to moisturizers in patients with more than one symptom [10], this study adds support for the use of vaginal moisturizers for mild to moderate GSM.…”
Section: Non-hormonal Therapymentioning
confidence: 99%
“…In a randomized trial of 172 postmenopausal individuals with vaginal dryness randomized to receive either a hormone-free vaginal moisturizer or vaginal estriol (0.1%) cream, the nonhormonal moisturizer was found to be noninferior to vaginal estriol for symptom improvement in women with mild to moderate symptoms [9 ▪ ]. Though earlier systematic review found that vaginal estrogen was superior to moisturizers in patients with more than one symptom [10], this study adds support for the use of vaginal moisturizers for mild to moderate GSM.…”
Section: Non-hormonal Therapymentioning
confidence: 99%